Digital Therapy Versus Traditional Care for Maternal Mental Health: Meta-Analysis of Psychotherapy RCTs - Audina, Angelina; Trias Mahmudiono; Siti Rahayu Nadhiroh; Emyr Reisha Isaura (Jurnal Kesehatan Masyarakat, 2025)
Perinatal mental health issues, particularly depression and anxiety, pose critical challenges to maternal and children’s well-being. It has been reported that psychological distress affects approximately 20.7% of prenatal and 17% of postnatal mothers, attributed to multifaceted emotional, physiological, social, and interpersonal transitions during the perinatal period. Accessibility of digital technologies has increased, prompting innovative approaches to prevention and treatment. This study aims to evaluate the effectiveness of digital psychotherapy interventions compared to traditional care in addressing perinatal mental health outcomes. A comprehensive literature search conducted between September and October 2023 across Scopus, PubMed, and Web of Science databases yielded eleven eligible randomized controlled trials (2017-2023). Meta-analytic findings using Review Manager 5.4 demonstrated significant reductions in anxiety (SMD: -0.41; 95% CI: -0.67 to -0.15; p = 0.002) and depressive symptoms (SMD: -0.41; 95% CI: -0.54 to -0.27; p < 0.00001) through digital interventions compared to traditional care. Future research directions should prioritize developing engaging interventions, possibly incorporating animation and virtual environments, while considering population-specific factors and optimal intervention duration.